Rare case of Parry-Romberg Syndrome (Hemi facial atrophy) - Karmacharya, BM; Karmacharya, RM (Journal of Institute of Medicine Nepal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Parry-Romberg syndrome is a rare syndrome that is more common in females. It is characterized by gradual onset and progressive atrophy of one half of face causing considerable disfigurement, blindness and orthodontic problems. The etiology and treatment has not been clarified yet. We report a case of this rare syndrome. Key Words: Hemi facial atrophy, Parry-Romberg Syndrome The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 36-37